![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a.
\(\frac{x-1}{x-5}=\frac{6}{7}\)
\(\left(x-1\right)\times7=6\times\left(x-5\right)\)
\(7x-7=6x-30\)
\(7x-6x=-30+7\)
\(x=-23\)
b.
\(\frac{x^2}{6}=\frac{24}{25}\)
\(x^2=\frac{24}{25}\times6\)
\(x^2=\frac{144}{25}\)
\(x^2=\left(\pm\frac{12}{5}\right)^2\)
\(x=\pm\frac{12}{5}\)
Vậy \(x=\frac{12}{5}\) hoặc \(x=-\frac{12}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{x-2}{5}=\frac{3}{8}\)
(x-2).8=5.3
(x-2).8=15
x-2=15:8
x-2=\(\frac{15}{8}\)
x=\(\frac{15}{8}+2\)
x=\(\frac{31}{8}\)
b)\(\frac{x-1}{x+5}=\frac{6}{7}\)
(x-1).7=(x+5).6
7x-7=6x+30
7x=6x+30+7
7x=6x+37
7x-6x=37
x=37
c)\(\frac{x^2}{6}=\frac{24}{25}\)
\(x^2.25=6.24\)
\(x^2.25=144\)
\(x^2=144:25\)
\(x^2=\frac{144}{25}\)
\(x^2=\left(\frac{12}{5}\right)^2\)
\(x=\frac{12}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{x}{6}^2=\frac{24}{25}\)
\(\Rightarrow x^2.25=6.24\)
\(\Rightarrow x^2.25=144\)
\(\Rightarrow x^2=144\div25\)
\(\Rightarrow x^2=5,76=2,4^2=\left(-2,4^2\right)\)
\(\Rightarrow x\in\left\{2,4;-2,4\right\}\)
Vậy \(x\in\left\{2,4;-2,4\right\}\)
b) \(\frac{72-x}{7}=\frac{x-40}{9}\)
\(\Rightarrow\left(72-x\right).9=\left(x-40\right).7\)
\(\Rightarrow648-9x=7x-280\)
\(\Rightarrow\left(-280\right)-648\) \(=-9x-7x\)
\(\Rightarrow-928=-16x\)
\(\Rightarrow x=58\)
Vậy \(x=58\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{x-1}{x+5}=\frac{6}{7}\)
\(\Rightarrow7.\left(x-1\right)=6.\left(x+5\right)\)
\(\Rightarrow7x-7=6x+30\)
\(\Rightarrow7x-6x=7+30\)
\(\Rightarrow x=37\)
b) \(\frac{x^2}{6}=\frac{24}{25}\)
\(\Rightarrow25.x^2=24.6\)
\(\Rightarrow25.x^2=144\)
\(\Rightarrow x^2=144:25\)
\(\Rightarrow x^2=\frac{144}{25}\)
\(\Rightarrow x^2=\frac{12^2}{5^2}\)
\(\Rightarrow x^2=\frac{12}{5}^2\)
\(\Rightarrow x=\pm\frac{12}{5}\)
\(c,\frac{x-2}{x-1}=\frac{x+4}{x+7}\)
\(\Leftrightarrow(x-2)(x+7)=(x+4)(x-1)\)
\(\Leftrightarrow x^2+5x-14=x^2+3x-4\)
\(\Leftrightarrow x^2+5x-14-x^2+3x=-4\)
\(\Leftrightarrow\left[x^2-x^2\right]+5x-3x-14=-4\)
\(\Leftrightarrow2x-14=-4\)
\(\Leftrightarrow2x=10\Leftrightarrow x=5\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{16}{2^x}=1\Leftrightarrow2^x=16\Leftrightarrow2^x=2^4\Leftrightarrow x=4\)
b)\(5^{x+2}=625\Leftrightarrow5^{x+2}=5^4\Leftrightarrow x+2=4\Leftrightarrow x=2\)
c)\(\frac{x+3}{8}=\frac{2}{x-3}\left(đk:x\ne3\right)\Leftrightarrow\left(x+3\right).\left(x-3\right)=2.8\Leftrightarrow x^2-9=16\Leftrightarrow x^2=25\Leftrightarrow\orbr{\begin{cases}x=5\\x=-5\end{cases}}\)
d)\(\frac{x^2}{6}=\frac{24}{25}\Leftrightarrow25x^2=24.6\Leftrightarrow\left(5x\right)^2=144\Leftrightarrow\orbr{\begin{cases}5x=12\\5x=-12\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{12}{5}\\x=-\frac{12}{5}\end{cases}}\)
a) 16=2^x \(\Leftrightarrow\)x=4
b)5^x+2=5^4\(\Leftrightarrow\)x+2=4\(\Leftrightarrow\)x=2
k đi, mk làm tiếp cho
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{11}{10,5}=\frac{6,32}{-x}\)
\(6,32:\frac{11}{10,5}=x\)
\(\frac{1659}{275}=x\)
b) \(\frac{x-1}{x+5}=\frac{6}{7}\)
\(\Rightarrow7x-7=6x+30\)
\(7x-6x=30+7\)
\(x=37\)
c) \(\frac{x^2}{6}=\frac{24}{25}\)
\(x^2=\frac{144}{25}\)
\(x=\frac{12}{5}\)
d) \(x:0,16=9:x\)
\(\frac{x}{0,16}=\frac{9}{x}\)
\(x^2=1,44\)
\(x=1,2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, ( 152 +và 2/4 - 148 và 3/8 ) : 0,2 = x : 0,3
=> 33/8 : 1/5 = x : 3/10
=> x : 3/10 = 165/8
=> x = 99/10
b, ( 85 và 7/30 - 83 và 5/18 ) : 2 và 2/3 = 0,01x : 4
=> 88/45 : 8/3 = 0,01x : 4
=> 0,01x : 4 = 11/15
=> 0,01x = 44/15
=> x = 880/3
c, x - 1/ x + 5 = 6/7
=> 7( x - 1 ) = 6( x + 5 )
=> 7x - 7 = 6x + 30
=> 7x - 6x = 7 + 30
=> x = 37
d, x2/6 = 24/25
=> x2. 25 = 6 . 24
=> x2.25 = 144
=> x2 = 144/25
=> x = ( 12/5)2 hoặc x = ( -12/5)
g, x - 3/ x + 5 = 5/7
=> 7( x - 3 ) = 5 ( x + 5 )
=> 7x - 21 = 5x + 25
=> 7x - 5x = 21 + 25
=> 2x = 46
=> x = 23
Ta có:
\(\frac{x^2}{6}=\frac{24}{25}\Leftrightarrow x^2.25=24.6\)
\(\Leftrightarrow x^2=\frac{24.6}{25}=\frac{144}{25}=5,76\)
\(\Leftrightarrow x=\sqrt{5,76}=2,4;x=-\sqrt{5,76}=-2,4\)
Vậy \(x=2,4\) hoặc \(x=-2,4\)